The use of cognitive agent programs in management support - Wuczyński, Maciej; Golec, Paweł; Hernes, Marcin; Rot, Artur; Gryncewicz, Wiesława; Fojcik, Marcin; Franczyk, Bogdan; Dyvak, Mykola (Wykorzystanie kognitywnych programów agentowych we wspomaganiu zarządzania, 2020)
A modern economy, based on information and knowledge, forces organizations to use IT tools that support management processes. The authors presented the concept of using cognitive agent programs to support management. These programs are able to track economic phenomena and processes taking place in the organization and its environment, conduct an in-depth analysis of information, draw conclusions and take specific actions. The features of cognitive agents allow organizations to gain a competitive advantage by making the right decisions faster at the operational, tactical and strategic level and by limiting the impact of such human characteristics as emotions or fatigue on task execution. The first part of the article outlines a characterisation of cognitive agent programs. The management areas in which cognitive agents can be used are then analysed and presented. The final part of the article provides conclusions and further research work
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 3 (57), s. 73-82
Keywords: cognitive agents; decision support; agent learning; use of cognitive agents; agenty kognitywne; wspomaganie decyzji; uczenie się agentów; zastosowanie agentów kognitywnych